A review and redefinition of the subgenus Aphyobranchius Wildekamp, 1977, in the seasonal killifish genus Nothobranchius Peters, 1868 (Teleostei: Nothobranchiidae), from ephemeral wetlands of eastern Tanzania - Watters, Brian R.; Nagy, Béla (Zootaxa, 2025)
Species belonging to the subgenus Aphyobranchius, of the seasonal killifish genus Nothobranchius, are reviewed and the definition of the subgenus is updated. Five species are recognized within this subgenus which, based primarily on morphological and molecular data, form two distinct groups: N. geminus, N. janpapi and N. luekei make up the N. janpapi species group, whereas N. fuscotaeniatus and N. lourensi comprise the N. lourensi species group. All known Aphyobranchius species occur in the central eastern and southern coastal plains region of Tanzania, associated mainly with the Ruvu, Rufiji, Kilombero, Mbezi and Luhule/Luhute river systems, with isolated occurrences in the lowermost reaches of the Wami and Matandu rivers. Features that allow distinction between the five Aphyobranchius species, as well as those that in a broader sense distinguish them from other Nothobranchius species, are documented in detail. Such features primarily comprise differences in elements of colour pattern, morphometric character, phylogenetic relationships, karyotype structure, habitat characteristics and niche preference, breeding behaviour and, to some extent, distribution. We further discuss the taxonomic, biogeographic, ecological and evolutionary aspects of the subgenus. Conservation status of the species range from Least Concern to Critically Endangered, according to IUCN Red List criteria. The main threats to their survival are habitat loss due to expansion of agriculture and urbanisation involving overexploitation of wetlands, and invasive species. Nothobranchius willerti, previously regarded as a member of Aphyobranchius, is here excluded from that subgenus, based on a reassessment of key morphological characters, habitat preference, breeding behaviour and, most importantly, molecular data that indicates a clear affiliation with other species of the subgenus Adiniops.